International Conference on Military Technologies (ICMT) 2015 2015
DOI: 10.1109/miltechs.2015.7153648
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic characteristics of airfoil with single plain flap for light airplane wing

Abstract: A numerical study was performed on a NACA 23012 airfoil with a single plain flap to examine the aerodynamic coefficients at Reynolds number of 3×10 6 , and to help for identifying the forces acting on a light airplane wing. Besides, in the paper the flow fields around the airfoil with single plain flap were shown. All calculations were made using a CFD code. For a turbulent model the Spalart-Allmaras method was chosen. Conclusions were made about the aerodynamic efficiency of the proposed configuration wing-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The simulation process can be divided into three parts, namely: Pre-processing, processing, and post-processing. The test object uses a Cessna C208b Grand Caravan wing with dimensions of 1:1 to the actual dimensions and flap geometry based on Todorov's research [8] so that the results obtained can be validated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation process can be divided into three parts, namely: Pre-processing, processing, and post-processing. The test object uses a Cessna C208b Grand Caravan wing with dimensions of 1:1 to the actual dimensions and flap geometry based on Todorov's research [8] so that the results obtained can be validated.…”
Section: Methodsmentioning
confidence: 99%
“…Some experts who have examined the dynamics of fluid flow in slotted flaps include Kasim [3], Chapman [4], Foster [5], Velkova [6,7], and others. Todorov [8] conducted research single slotted flaps for light airplane wings. The method that will be used in this study is a two-dimensional numerical simulation using fluent software.…”
Section: Introductionmentioning
confidence: 99%
“…Wenzinger [9] tested various flap types in a wind tunnel, with the slotted flap showing one of the largest increases in C L . Todorov [10] and Hussein et al [11] found increased C L and C D values in simulations by modifying airfoils with a slotted flap. Prabhakar and Ohri [12] found good agreement in C L between their 3D simulation of a plain NACA 2412 and wind tunnel data from Saha [13]; they did not compare their 3D model to a 2D one.…”
Section: Introductionmentioning
confidence: 98%
“…A numerical analysis was conducted by Michael Todorov [16] concluded that the slotted wing had more significant lift force than that from the normal wing. The unsteady wind flow around a symmetric aerofoil was conducted numerically by Kurtulus [17].…”
Section: Introductionmentioning
confidence: 99%